Concomitant mortality trends due to obesity and hypertension in the U.S.: a 20-year retrospective analysis of the CDC WONDER database - Rayyan Nabi; Alina Zanub; Muzamil Akhtar; Sohaib Aftab Ahmad Chaudhry; Abdul Raffay Awais; Hanzala Ahmed Farooqi; Sabahat Ul Ain Munir Abbasi; Peter Collins; Tabeer Zahid; Raheel Ahmed; Muhammad Zia Ur Rehman (BMC Cardiovascular Disorders)
Abstract Background Hypertension (HTN) and obesity are leading, interrelated risk factors for cardiovascular disease, stroke, and kidney disease in the United States. Despite advances in medical therapies and public health interventions, the joint mortality burden associated with these conditions remains substantial. We sought to characterize national trends and demographic disparities in obesity- and hypertension-related mortality from 2000 to 2019 using the CDC WONDER database. Methods In this retrospective descriptive study, multiple cause-of-death data for individuals aged ≥ 25 years were extracted from CDC WONDER. Obesity (ICD-10 E66.*) and hypertension (ICD-10 I10–I15)-related deaths were identified as underlying or contributing causes. Crude Mortality Rates (CMRs) and Age-Adjusted Mortality Rates (AAMRs) per 100,000 population were calculated annually and standardized to the 2000 U.S. population. Joinpoint regression was employed to estimate Annual Percent Change (APC) and Average Annual Percent Change (AAPC) in AAMRs, with statistical significance set at p < 0.05. Trends were stratified by sex, race/ethnicity, urban-rural classification, and U.S. Census region. Results From 2000 to 2019, there were 254,116 obesity- and hypertension-related deaths (54.6% male). The combined AAMR rose from 2.58 to 9.62 per 100,000 (AAPC 7.31*, 95% CI 6.66–7.97). Men experienced higher AAMRs than women (AAPC 8.50* vs. 6.08*, respectively). Non-Hispanic Black individuals exhibited the highest AAMR (11.19), followed by American Indian/Alaska Native (6.62) and non-Hispanic White (5.35) populations. Non-metropolitan counties demonstrated greater mortality (AAMR 6.52) compared to metropolitan areas (5.76), and Southern and rural states bore the highest burdens. Conclusions Over two decades, obesity- and hypertension-related mortality in U.S. adults has increased significantly across all demographic groups, with pronounced disparities by sex, race/ethnicity, and rurality. Targeted, multifaceted interventions are urgently needed to curb this growing public health crisis.